Discovering leadership designing your success - Middlebrooks, Anthony E.; Allen, Scott J.; McNutt, Scott J.; Morrison, James L. (SAGE, 2020)
Discovering Leadership: Designing Your Success by Anthony Middlebrooks, Scott J. Allen, Mindy Mc Nutt, and James Morrison provides a practical, engaging foundation and easy-to-understand framework for individuals to purposefully design leadership. This action-oriented text starts with the self and helps students understand their individual strengths, styles, and skills with numerous reflection opportunities. Next, the text explores the relational aspects of leadership and best practices for motivating and inspiring followers. Finally, the text concludes by examining how leaders can transform their communities and create lasting, positive change. Practical applications and activities in each chapter help students develop their confidence, optimism, resiliency, and engagement. Regardless of your students’ background or major, they will gain the knowledge and skills they need to become thoughtful, impactful leaders.